MTHFR Gene Polymorphisms in Iraqi Kurdish Rheumatoid Arthritis Patients: Relation to Methotrexate Response and Toxicity - Younis, Sherzad Saeed; Issa, Najlaa Kadhm; Sulaiman, Dhia Mustafa (Iraqi Journal of Science, 2022)
Methotrexate (MTX) is still one of the gold standard treatments for rheumatoid arthritis (RA). It shows diverse outcomes in blood level and clinical response, this was demonstrated by its relation to the genetic polymorphism in the pharmacogenetic study. This study aimed to investigate the role of methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms in relation to MTX efficacy and toxicity in Iraqi Kurdish RA patients. Sixty-four RA patients were involved in this study with an average age of 47.78 ±14.08 and female to male ratio of (8.1). Diagnosis and disease activity were confirmed. Blood analyses, including those of laboratory markers of disease activity, were done. The 28 joint disease activity score (DAS28-CRP) was calculated. MTHFR gene polymorphisms were analyzed by real-time polymerase chain reaction. The most frequent genotypes which were identified in RA patients were the CT genotype of the C677T single nucleotide polymorphism (SNP) (51.6%) and the AC genotype of the A1298C SNP (48.4%). Patients with non-response to treatment had high frequencies of genotypes CT and TT (58.0% and 12.0%) of the C677T SNP respectively, as compared to those in the responder group; 28.6% and 0.0%); T-allele was associated with drug non-responding OR=4.17, P value=.0.009, meanwhile; genotypes AC and CC of the A1298C SNP were seen in (54.0% and 16.0%) in non-responder group. Patients with active RA had increased frequencies of CT and TT genotypes of the C677T SNP (60.0% and16.0%) respectively as compared to those who were in remission (26.6% and 0.0%); T-allele was associated with high disease activity; OR = 5.11. No association was found between C677T SNP and A1298C SNP, and MTX level status (P> 0.05). However, the variant alleles (T and C) were associated with the MTX toxic level (OR: 2.05, 95% CI [0.97 – 4.32]) and (OR: 1.99, 95% CI [0.96 – 4.18]) respectively. This study suggests that genetic polymorphisms of MTHFR SNP (C677T and A1298C) are associated with MTX efficacy but not toxicity in RA patients. This may assist the physicians in personalizing RA treatment in Iraqi patients.